2013
DOI: 10.1038/aja.2013.89
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent tri-weekly docetaxel plus bicalutamide in patients with castration-resistant prostate cancer: a single-arm prospective study using a historical control for comparison

Abstract: Whether continuous docetaxel (DTX) chemotherapy offers an advantage over intermittent therapy for castration-resistant prostate cancer (CRPC) is unknown. In this study, we evaluated the efficacy, toxicity and quality of life (QoL) of intermittent tri-weekly DTX with bicalutamide in CRPC. Forty-two patients (group A) with CRPC were enrolled. The patients received intravenous DTX (75 mg m 22 ) once tri-weekly with oral bicalutamide (50 mg) once daily. Patients had a DTX holiday when the prostate-specific antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…This is comparable to the median duration of the first treatment holidays found in other studies: 18 weeks (range 4–70) for patients in the Androgen‐independent prostate cancer Study of Calcitriol ENhancing Taxotere (ASCENT) trial who received intermittent docetaxel plus either calcitriol or placebo (45/250 patients) and 5.3 months (range 2–20) reported by Li et al. , which dropped to 2.8 months (range 1–7) in the second holiday; 67% of patients (28/42) with intermittent treatment reached the first docetaxel holiday and the therapy was well tolerated.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This is comparable to the median duration of the first treatment holidays found in other studies: 18 weeks (range 4–70) for patients in the Androgen‐independent prostate cancer Study of Calcitriol ENhancing Taxotere (ASCENT) trial who received intermittent docetaxel plus either calcitriol or placebo (45/250 patients) and 5.3 months (range 2–20) reported by Li et al. , which dropped to 2.8 months (range 1–7) in the second holiday; 67% of patients (28/42) with intermittent treatment reached the first docetaxel holiday and the therapy was well tolerated.…”
Section: Discussionsupporting
confidence: 82%
“…Data on intermittent vs continuous docetaxel treatment is limited. The efficacy of an intermittent docetaxel therapy or docetaxel rechallenge has been tested in a few retrospective studies and in one prospective one-armed study with a historical control group [25][26][27][28]. These studies observed median OS of 15.8-19 months for intermittent docetaxel, corresponding well to the OS seen in the present study, with one exception where a median OS of 13 months was stated [25], probably due to higher age of enrolled patients [26][27][28].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In addition, it was reported that MRP4 expression levels increased with androgen treatment, but decreased with anti-androgen treatment, in LNCaP cells (25). Furthermore, our previous study demonstrated that DTX-resistance time in patients with low testosterone levels was significantly delayed compared with that in patients with high testosterone levels (26). These data indicated that androgen levels may be associated with DTX resistance.…”
Section: Introductionmentioning
confidence: 65%